Perceived benefits of green logistics practices from the perspective of Malaysian foodbased manufacturers. - Hussin, Hilda; Kamarulzaman, Nitty Hirawaty; Abdullah, Amin Mahir; Abd Rahman, Azmawani (2012)

(untitled)
Over the past 50 years, logistics has been regarded as a key determinant of business performance. However, increase in environmental concerns, which cover greatly on pollution, climate change, congestion, waste disposal, and resource depletion have triggered increased attention from the government and society. Business operations, such as sourcing, manufacturing and logistics are believed to be responsible for most of the environmental problems. Besides, the growing demand of customers and environmental societies for more environmental friendly products have led ‘green’ becomes a common practice to portray the environmental friendly image of products, processes, systems and technologies, and the way business is conducted. Thus, green logistics is concerned with producing and distributing goods in a sustainable way, taking account of environmental and social factors. It also refers to a sustainable logistics which suggests compatibility with the environment. Companies must adopt new environmental policies and carry out sustainable activities as competitive advantage strategies for business survival. This paper investigates how Malaysian agro-based manufacturers perceive benefits of green logistics practices. The directory of Federation of Malaysian Manufacturer (FFM) was used to obtain details from the respondents. Data was collected through a survey and analyzed using descriptive analysis, means ranking, correlation analysis and T-test analysis. The findings suggested that benefits obtained by the manufacturers can be categorized into three main groups namely economy, environment and social.